steel

JP2026143233APending Publication Date: 2026-09-08NIPPON STEEL CORPORATION
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2025030718
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2026-09-08

AI Technical Summary

Benefits of technology

【0014】 本開示による鋼材では、浸炭処理が施されて浸炭鋼部品とした場合に、優れた低サイクル疲労強度が得られる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026143233000004
    Figure 2026143233000004
  • Figure 2026143233000005
    Figure 2026143233000005
  • Figure 2026143233000006
    Figure 2026143233000006
Patent Text Reader

Abstract

The present invention provides a steel material that, when subjected to carburizing treatment to become a carburized steel component, exhibits excellent low-cycle fatigue strength. [Solution] The composition is as follows (by mass%): C: 0.10-0.30%, Si: 0.65-2.00%, Mn: 0.48-1.00%, P: 0.035% or less, S: 0.035% or less, Cr: 0.80-2.00%, Al: 0.010-0.050%, N: 0.0020-0.0200%, and Mo: 0.10-0.35%, with the remainder being Fe and impurities, satisfying formula (1), and in the microstructure, the area ratio of ferrite is 50-70%, the area ratio of bainite is 20% or less, with the remainder being pearlite, the average equivalent circle diameter of the ferrite grains is 40 μm or less, and the standard deviation of the equivalent circle diameter of the ferrite grains is 10 μm or less. 3.5≦(8Mn+3Cr) / (Si+5Mo)≦6.8 (1)
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This disclosure relates to steel materials, and more particularly to steel materials suitable for carburized machine structural components (hereinafter also referred to as carburized steel components). [Background technology]

[0002] Mechanical structural components such as gears and shafts used in power sources and power transmission mechanisms of automobiles and industrial machinery engines require high fatigue strength. To improve fatigue strength, mechanical structural components are sometimes subjected to surface hardening treatments. Among the various surface hardening treatments, mechanical structural components are sometimes subjected to carburizing treatment. Carburized mechanical structural components (carburized steel components) are widely used as parts for automobiles and industrial machinery.

[0003] Japanese Patent Publication No. 2005-325398 (Patent Document 1) proposes a technique for increasing the fatigue strength of carburized steel parts.

[0004] The high-strength gear disclosed in Patent Document 1 is made of steel material formed into a gear shape by forging or machining, containing, by mass%, C: 0.10-0.25%, Si: 0.8-1.2%, Mn: 0.6-2.0%, S: 0.006% or more, Cr: 1.0-2.0%, Mo: 0.2-0.8%, Al: 0.005-0.200%, and N: 0.0050-0.0200%, with the remainder being Fe and unavoidable impurities. After being formed into a gear shape, the C content of the surface layer is less than 0.9% by mass when subjected to carburizing or carbonitriding treatment. The amount of retained austenite from the surface layer to a depth of 100 μm of the gear is 40% by volume or less. Furthermore, the microstructure is single-phase martensite. Patent Document 1 states that this gear increases the resistance to tempering softening by increasing the amount of Si and Cr in the steel, and further suppresses softening due to heat generation at the gear contact surface. Furthermore, by appropriately controlling the microstructure of the carburized surface and the C content of the surface layer, the tooth root bending fatigue strength and surface pressure fatigue strength are increased.

[0005] Incidentally, in recent years, with the increasing power output of engines and the miniaturization of parts, even higher fatigue strength is required for carburized steel parts used in gears for automobiles and construction vehicles. Among carburized steel parts, gears used in automobile differential gears, etc., are subjected to strong impacts when the car is suddenly accelerating or braking, and when the vehicle's tires collide with protrusions such as stones on the road surface. When subjected to strong impacts, even if the frequency of impacts is low, carburized steel parts may break. Therefore, carburized steel parts used in this application require 10 2 ~10 4 Excellent low-cycle fatigue strength with a high number of repetitions is particularly required.

[0006] In Patent Document 1, 10 7 Improvements to fatigue strength in high cycles have been studied. However, Patent Document 1 states that 10 2 ~10 4 The low-cycle fatigue strength for each cycle has not been studied.

[0007] Japanese Patent Publication No. 2020-094231 (Patent Document 2) proposes a technique for increasing low-cycle fatigue strength.

[0008] The carburized steel part disclosed in Patent Document 2 contains, by mass%, C: 0.10%~0.30%, Si: 0.70%~1.20%, Mn: 0.30%~1.00%, Cr: 0.15%~1.25%, Mo: 0.80% or less, Al: 0.020%~0.050%, and N: 0.0030%~0.0200%, with the remainder being Fe and unavoidable impurities. This part has a carburized layer on its surface. In the manufacturing process of this part, during the tempering treatment after carburizing and quenching, the treatment temperature T (°C) satisfies the following equations (1) and (2). Here, equation (1) is T (°C) ≥ 200 - 4[Si] - 29[Mo]. Equation (2) is 100[Si] + 45[Mo] + 180 ≥ T (°C). Patent Document 2 states that by performing a tempering treatment on this part at temperatures that satisfy the above equations (1) and (2), the high-cycle bending fatigue strength and low-cycle bending fatigue strength are increased. [Prior art documents] [Patent Documents]

[0009] [Patent Document 1] Japanese Patent Publication No. 2005-325398 [Patent Document 2] Japanese Patent Publication No. 2020-094231 [Overview of the project] [Problems that the invention aims to solve]

[0010] Patent Document 2 states that 10 7 Not only fatigue intensity in high cycles, but also 10 2 The low-cycle fatigue strength in a given number of cycles is disclosed. However, there may be steel materials that can be made into carburized steel parts by means other than those disclosed in Patent Document 2, which are subjected to carburizing treatment.

[0011] The purpose of this disclosure is to provide a steel material that, when subjected to carburizing treatment to become a carburized steel part, exhibits excellent low-cycle fatigue strength. [Means for solving the problem]

[0012] The steel materials disclosed herein are In mass%, C: 0.10~0.30%, Si: 0.65~2.00%, Mn: 0.48~1.00%, P: 0.035% or less, S: 0.035% or less, Cr: 0.80~2.00%, Al: 0.010~0.050%, N: 0.0020 to 0.0200%, and, It contains Mo: 0.10~0.35%, The remainder consists of Fe and impurities. Satisfying equation (1), In the microstructure, the area fraction of ferrite is 50 to 70%, the area fraction of bainite is 20% or less, and the balance consists of pearlite, the average equivalent circular diameter of the ferrite crystal grains is 40 μm or less, and the standard deviation of the equivalent circular diameter of the ferrite crystal grains is 10 μm or less. 3.5≦(8Mn+3Cr) / (Si+5Mo)≦6.8 (1) Here, for each element symbol in formula (1), the content of the corresponding element in said chemical composition is substituted in mass%.

[0013] The steel material according to the present disclosure is in mass%, C: 0.10 to 0.30%, Si: 0.65 to 2.00%, Mn: 0.48 to 1.00%, P: 0.035% or less, S: 0.035% or less, Cr: 0.80 to 2.00%, Al: 0.010 to 0.050%, N: 0.0020 to 0.0200%, and Mo: 0.10 to 0.35%, further contains one or more selected from the group consisting of the first group and the second group, the balance consists of Fe and impurities, satisfies formula (1), in the microstructure, the area fraction of ferrite is 50 to 70%, the area fraction of bainite is 20% or less, and the balance consists of pearlite, the average equivalent circular diameter of the ferrite crystal grains is 40 μm or less, and the standard deviation of the equivalent circular diameter of the ferrite crystal grains is 10 μm or less. [First Group] Cu: 0.40% or less, Ni: 0.30% or less, Mg: 0.0050% or less, V: 0.50% or less, Nb: 0.050% or less, Ti: 0.050% or less, Ca: 0.0020% or less, B: Select one or more from the group consisting of 0.0040% or less. [Group 2] Bi: 0.020% or less, Pb: 0.060% or less, Sn: 0.100% or less, Sb: 0.050% or less, and, One or more selected from the group consisting of As: 0.050% or less. 3.5≦(8Mn+3Cr) / (Si+5Mo)≦6.8 (1) Here, each element symbol in equation (1) is substituted with the content of the corresponding element in the aforementioned chemical composition, expressed in mass percent. [Effects of the Invention]

[0014] The steel material according to this disclosure, when subjected to carburizing treatment to become a carburized steel part, exhibits excellent low-cycle fatigue strength. [Brief explanation of the drawing]

[0015] [Figure 1] Figure 1 is a magnified optical microscope image showing ferrite and pearlite in the microstructure of the steel material of this embodiment. [Figure 2] Figure 2 is a magnified optical microscope image showing ferrite and bainite in the microstructure of the steel material of this embodiment. [Figure 3] Figure 3 shows the top, side, and front views of the test specimen used to measure low-cycle fatigue strength. [Figure 4] Figure 4 is an enlarged view of the test area in the specimen used to measure the low-cycle fatigue strength shown in Figure 3. [Modes for carrying out the invention]

[0016] First, the inventors investigated and examined the low-cycle fatigue strength of carburized steel parts. As a result, they obtained the following findings.

[0017] Parts requiring high cycle fatigue strength are subjected to load at a number of repetitions exceeding 10 4 cycles. However, the load that such parts receive per cycle is small. On the other hand, for parts requiring low cycle fatigue strength, the number of repetitions is as low as 10 4 cycles or less. However, the load that such parts receive per cycle is large. Therefore, although parts requiring low cycle fatigue strength are subjected to load less frequently than parts requiring high cycle fatigue strength, they are required to have strength that can withstand large loads (impacts).

[0018] Based on the above findings, the present inventors first investigated, from the viewpoint of chemical composition, steel materials that can provide excellent low cycle fatigue strength when formed into carburized steel parts. The results show that, in mass%, C: 0.10 to 0.30%, Si: 0.65 to 2.00%, Mn: 0.48 to 1.00%, P: 0.035% or less, S: 0.035% or less, Cr: 0.80 to 2.00%, Al: 0.010 to 0.050%, N: 0.0020 to 0.0200%, Mo: 0.10 to 0.35%, Cu: 0 to 0.40%, Ni: 0 to 0.30%, Mg: 0 to 0.0050%, V: 0 to 0.50%, Nb: 0 to 0.050%, Ti: 0 to 0.050%, Ca: 0 to 0.0020%, B: 0 to 0.0040%, Bi: 0 to 0.020%, Pb: 0 to 0.060%, Sn: 0 to 0.100%, Sb: 0 to 0.050%, and As: 0 to 0.050%, with the balance being Fe and impurities, it was considered that such a steel material may provide excellent low cycle fatigue strength when formed into a carburized steel part.

[0019] The present inventors further focused their attention on the hardened layer of carburized steel parts. As described above, parts requiring low cycle fatigue strength are expected to be subjected to large loads. Therefore, parts requiring low cycle fatigue strength are required to suppress the occurrence of cracks caused by large loads (impacts). A hardened layer having a high carbon concentration and a martensite-dominant microstructure is formed on the surface layer of a carburized steel part. It is considered that if the hardened layer has high durability against impact, the occurrence of cracks caused by large loads (impacts) can be suppressed.

[0020] Based on the above considerations, the inventors investigated the microstructure of the quenched layer formed on the surface of carburized steel parts. As mentioned above, the quenched layer has a microstructure mainly composed of martensite. If the prior austenite grains are too large in the microstructure of the quenched layer, the quenched layer becomes prone to cracking when subjected to a large load (impact). As a result, the low-cycle fatigue strength of the carburized steel part decreases. Furthermore, if there is a large variation in the size of the prior austenite grains in the microstructure of the quenched layer, stress will concentrate locally when the quenched layer is subjected to a large load (impact). Cracks are more likely to occur at the locations where stress is concentrated. As a result, the low-cycle fatigue strength of the carburized steel part decreases.

[0021] Based on the above considerations, the inventors believe that if the coarsening of prior austenite grains in the quenched layer formed on the surface of the carburized steel part can be suppressed, and furthermore, if the variation in the size of the prior austenite grains can be suppressed, the low-cycle fatigue strength of the carburized steel part can be increased.

[0022] Incidentally, the size and variation of prior austenite grains in the microstructure of the quenched layer are influenced by the microstructure of the steel material used to make the carburized steel parts. When the content of each element in the chemical composition of the steel material is within the above range, the microstructure of the steel material may consist of ferrite, pearlite, and bainite. Here, bainite is a factor that causes variation in the prior austenite grains in the microstructure of the quenched layer after carburizing and quenching. Therefore, it is preferable that the microstructure of the steel material has a bainite area ratio as small as possible and is mainly composed of ferrite and pearlite.

[0023] On the other hand, even when the microstructure is mainly composed of ferrite and pearlite, it has been found that an excessive area ratio of ferrite or pearlite can cause the prior austenite grains in the quenched layer after carburizing and quenching to become inconsistent. Therefore, the inventors considered that there is an appropriate range not only for reducing the area ratio of bainite, but also for the area ratios of ferrite and pearlite, and conducted investigations accordingly.

[0024] As a result, it was found that in the microstructure of steel materials where the content of each element in the chemical composition is within the above range, if the ferrite area ratio is 50-70%, the bainite area ratio is 20% or less, and the remainder consists of pearlite, then the variation in the size of prior austenite grains caused by bainite in the microstructure of the quenched layer can be suppressed.

[0025] The inventors further investigated the relationship between ferrite grains (hereinafter also referred to as ferrite grains) and pearlite grains (hereinafter also referred to as pearlite grains) in steel. Ferrite and pearlite in steel transform into austenite during heating in carburizing treatment, and then transform into martensite during quenching. Therefore, if the size of the ferrite grains and pearlite grains in the steel is coarse, the prior austenite grains in the microstructure of the quenched layer will also be coarse. Furthermore, if the sizes of the ferrite grains and pearlite grains differ significantly, the size of the prior austenite grains in the microstructure of the quenched layer will vary. Therefore, it is preferable that the size of the ferrite grains and pearlite grains in the steel is appropriately controlled, and that the variation in the size of the ferrite grains and pearlite grains is suppressed. In this specification, a pearlite grain is defined as a single pearlite block that is spaced apart from other pearlite blocks, or as a group of pearlite blocks that are continuously connected.

[0026] The inventors investigated the adjustment of the size of ferrite and pearlite grains. As a result, assuming that the content of each element in the chemical composition is within the above range and the microstructure is within the above range, they found that by satisfying the following conditions A and B, the size of ferrite and pearlite grains in the steel material can be adjusted, suppressing the coarsening and size variation of prior austenite grains in the quenched layer formed on the surface of the carburized part, and resulting in excellent low-cycle fatigue strength. (Condition A) The following equation (1) is satisfied. 3.5≦(8Mn+3Cr) / (Si+5Mo)≦6.8 (1) In equation (1), each element symbol is substituted with the corresponding element content in the chemical composition, expressed in mass percent. (Condition B) The average equivalent circle diameter of the ferrite grains is 40 μm or less, and the standard deviation of the equivalent circle diameter of the ferrite grains is 10 μm or less.

[0027] Let F1 be defined as F1 = (8Mn + 3Cr) / (Si + 5Mo). If F1 satisfies the above equation (1), the low-cycle fatigue strength of the carburized steel part will increase. The reason for this is not entirely clear, but the following reasons are possible. Mn and Cr are elements that affect the coarsening of pearlite grains (hereinafter referred to as pearlite coarsening contributing elements). Si and Mo are elements that affect the coarsening of ferrite grains (hereinafter referred to as ferrite coarsening contributing elements). If F1 is less than 3.5, the contribution of the ferrite coarsening contributing elements is greater than that of the pearlite coarsening contributing elements. In this case, the ferrite grains become coarser, while the pearlite grains become finer. Therefore, in the microstructure of the quenched layer, the prior austenite grains become coarser, and the variation in the size of the prior austenite grains increases. As a result, the low-cycle fatigue strength decreases.

[0028] On the other hand, if F1 exceeds 6.8, the contribution of elements contributing to pearlite coarsening is greater than that of elements contributing to ferrite coarsening. In this case, pearlite grains become coarser, while ferrite grains become finer. Therefore, in the microstructure of the quenched layer, prior austenite grains become coarser, and the variation in the size of prior austenite grains increases. As a result, the low-cycle fatigue strength decreases.

[0029] It should be noted that a mechanism other than the one described above may also be at work. However, the fact that low-cycle fatigue strength increases when F1 satisfies equation (1) above has been demonstrated in the examples described later.

[0030] If F1 satisfies formula (1) above, then, assuming that the content of each element in the chemical composition of the steel is within the above range, both ferrite grains and pearlite grains in the steel are refined. On the other hand, even when F1 satisfies formula (1) above, there were cases where the coarsening of prior austenite grains in the quenched layer formed on the surface of the carburized steel part was not sufficiently suppressed. Therefore, the inventors conducted further investigations from the viewpoint of the microstructure of the steel. As a result, it was found that by making the average equivalent circle diameter of the ferrite crystal grains 40 μm or less, the ferrite grains and pearlite grains in the steel are sufficiently refined. This suppresses the coarsening of prior austenite grains in the quenched layer formed on the surface of the carburized steel part.

[0031] Here, even if F1 satisfies equation (1) above and the average equivalent circle diameter of the ferrite grains is 40 μm or less, if the standard deviation of the equivalent circle diameter of the ferrite grains exceeds 10 μm, the variation in the size of the ferrite grains is not sufficiently suppressed. In this case, even if the average equivalent circle diameter of the ferrite grains is 40 μm or less, the variation in the size of the prior austenite grains in the quenched layer formed on the surface of the part after carburizing treatment will be large. By setting the standard deviation of the equivalent circle diameter of the ferrite grains to 10 μm or less, the variation in the size of the microstructure of the steel material can be suppressed. Furthermore, if F1 satisfies equation (1) above, and the average equivalent circle diameter of the ferrite grains and the standard deviation of the equivalent circle diameter of the ferrite grains are appropriately set, not only the ferrite grains but also the pearlite grains can be sufficiently refined, and the variation in the size of the pearlite grains can be suppressed.

[0032] Therefore, by setting F1 to 3.5-6.8, keeping the average equivalent circle diameter of the ferrite grains to 40 μm or less, and adjusting the standard deviation of the equivalent circle diameter of the ferrite grains to 10 μm or less, assuming that the content of each element in the chemical composition of the steel is within the above range and the microstructure of the steel is within the above range, the ferrite and pearlite grains in the steel will not become excessively coarse and will be of an appropriate size. Furthermore, the variation in the size of prior austenite grains in the quenched layer of the carburized steel parts after carburizing treatment will also be suppressed. As a result, the low-cycle fatigue strength will be increased.

[0033] The steel material of this embodiment was completed based on the above technical concept. The steel material according to this embodiment has the following configuration.

[0034] The steel material of the first component is In mass%, C: 0.10~0.30%, Si: 0.65~2.00%, Mn: 0.48~1.00%, P: 0.035% or less, S: 0.035% or less, Cr: 0.80~2.00%, Al: 0.010~0.050%, N: 0.0020 to 0.0200%, and, It contains Mo: 0.10~0.35%, The remainder consists of Fe and impurities. Satisfying equation (1), In the microstructure, the area ratio of ferrite is 50-70%, the area ratio of bainite is 20% or less, and the remainder consists of pearlite. The average equivalent diameter of the ferrite grains is 40 μm or less. The standard deviation of the equivalent circular diameter of the ferrite grains is 10 μm or less. 3.5≦(8Mn+3Cr) / (Si+5Mo)≦6.8 (1) Here, each element symbol in equation (1) is substituted with the content of the corresponding element in the aforementioned chemical composition, expressed in mass percent.

[0035] The steel material of the second component is, In mass%, C: 0.10~0.30%, Si: 0.65~2.00%, Mn: 0.48~1.00%, P: 0.035% or less, S: 0.035% or less, Cr: 0.80~2.00%, Al: 0.010~0.050%, N: 0.0020 to 0.0200%, and, It contains Mo: 0.10~0.35%, Furthermore, it contains one or more selected from the group consisting of Group 1 and Group 2, The remainder consists of Fe and impurities. Satisfying equation (1), In the microstructure, the area ratio of ferrite is 50-70%, the area ratio of bainite is 20% or less, and the remainder consists of pearlite. The average equivalent diameter of the ferrite grains is 40 μm or less. The standard deviation of the equivalent circular diameter of the ferrite grains is 10 μm or less. [Group 1] Cu: 0.40% or less, Ni: 0.30% or less, Mg: 0.0050% or less, V: 0.50% or less, Nb: 0.050% or less, Ti: 0.050% or less, Ca: 0.0020% or less, B: Select one or more from the group consisting of 0.0040% or less. [Group 2] Bi: 0.020% or less, Pb: 0.060% or less, Sn: 0.100% or less, Sb: 0.050% or less, and, One or more selected from the group consisting of As: 0.050% or less. 3.5≦(8Mn+3Cr) / (Si+5Mo)≦6.8 (1) Here, each element symbol in equation (1) is substituted with the content of the corresponding element in the aforementioned chemical composition, expressed in mass percent.

[0036] The third component is steel, A steel material of the second composition, The aforementioned chemical composition contains the first group.

[0037] The fourth component is steel, A steel material having a second or third configuration, The aforementioned chemical composition contains the second group.

[0038] The steel material according to this embodiment will be described in detail below. Unless otherwise specified, the "%" in relation to elements refers to "mass%".

[0039] [Features of the steel material of this embodiment] The steel material of this embodiment has the following features: (Feature 1) The chemical composition, in mass percent, is as follows: C: 0.10-0.30%, Si: 0.65-2.00%, Mn: 0.48-1.00%, P: ≤0.035%, S: ≤0.035%, Cr: 0.80-2.00%, Al: 0.010-0.050%, N: 0.0020-0.0200%, Mo: 0.10-0.35%, Cu: 0-0.40%, Ni: 0-0.30%. It contains Mg: 0-0.0050%, V: 0-0.50%, Nb: 0-0.050%, Ti: 0-0.050%, Ca: 0-0.0020%, B: 0-0.0040%, Bi: 0-0.020%, Pb: 0-0.060%, Sn: 0-0.100%, Sb: 0-0.050%, and As: 0-0.050%, with the remainder being Fe and impurities. (Feature 2) The equation (1) is satisfied. 3.5≦(8Mn+3Cr) / (Si+5Mo)≦6.8 (1) Here, each element symbol in equation (1) is substituted with the mass percentage of the corresponding element's content in the chemical composition. (Feature 3) In its microstructure, ferrite accounts for 50-70% of the area, bainite accounts for less than 20%, and the remainder consists of pearlite. (Feature 4) In the microstructure, the average equivalent circle diameter of the ferrite grains is 40 μm or less, and the standard deviation of the equivalent circle diameter of the ferrite grains is 10 μm or less. Features 1 through 4 are explained below.

[0040] [(Feature 1) Regarding chemical composition] The chemical composition of the steel wire in this embodiment contains the following elements:

[0041] C: 0.10~0.30% Carbon (C) enhances the hardenability of steel. As a result, the low-cycle fatigue strength of carburized steel parts made from steel is increased. If the C content is less than 0.10%, the above effect cannot be fully obtained, even if the content of other elements is within the range of this embodiment. On the other hand, if the carbon content exceeds 0.30%, the hardness of the steel becomes excessively high, even if the content of other elements is within the range of this embodiment. As a result, the machinability of the steel decreases. Therefore, the C content is 0.10-0.30%. The preferred lower limit for the C content is 0.15%, more preferably 0.17%, and even more preferably 0.19%. The preferred upper limit for the C content is 0.26%, more preferably 0.24%, and even more preferably 0.22%.

[0042] Si: 0.65~2.00% Silicon (Si) enhances the hardenability of steel. As a result, the low-cycle fatigue strength of carburized steel parts made from steel is increased. If the Si content is less than 0.65%, the above effect cannot be fully obtained, even if the content of other elements is within the range of this embodiment. On the other hand, if the Si content exceeds 2.00%, the hardness of the steel material will increase excessively, even if the content of other elements is within the range of this embodiment. As a result, the machinability of the steel material will decrease. Therefore, the Si content is 0.65-2.00%. The preferred lower limit for the Si content is 0.70%, more preferably 0.72%, and even more preferably 0.75%. The preferred upper limit for the Si content is 1.80%, more preferably 1.50%, more preferably 1.25%, more preferably 1.20%, and still more preferably 1.00%.

[0043] Mn: 0.48~1.00% Manganese (Mn) enhances the hardenability of steel. As a result, the low-cycle fatigue strength of carburized steel parts made from steel is increased. If the Mn content is less than 0.48%, the above effect cannot be fully obtained, even if the content of other elements is within the range of this embodiment. On the other hand, if the Mn content exceeds 1.00%, the hardness of the steel becomes excessively high, even if the content of other elements is within the range of this embodiment. As a result, the machinability of the steel decreases. Therefore, the Mn content is 0.48-1.00%. The preferred lower limit of the Mn content is 0.50%, more preferably 0.51%, and even more preferably 0.52%. The preferred upper limit for the Mn content is 0.98%, more preferably 0.90%, even more preferably 0.80%, and even more preferably 0.70%.

[0044] P:0.035% or less Phosphorus (P) is an impurity. P segregates at grain boundaries. As a result, grain boundary strength decreases. If the P content exceeds 0.035%, even if the content of other elements is within the range of this embodiment, P will excessively segregate at grain boundaries, reducing grain boundary strength. As a result, the low-cycle fatigue strength of carburized steel parts made from steel material will decrease. Therefore, the P content is 0.035% or less. The preferred upper limit for the P content is 0.030%, more preferably 0.025%, even more preferably 0.020%, and even more preferably 0.015%. A low phosphorus (P) content is preferable. However, excessive reduction of the P content increases manufacturing costs. Therefore, considering normal industrial production, the preferred lower limit of the P content is greater than 0%, more preferably 0.001%, more preferably 0.002%, more preferably 0.004%, and more preferably 0.009%.

[0045] S: 0.035% or less Sulfur (S) is an impurity. S generates sulfide inclusions. Coarse sulfide inclusions are prone to becoming the starting point for cracks during use in carburized steel parts made from steel. If the S content exceeds 0.035%, the sulfide inclusions will become coarse, even if the content of other elements is within the range of this embodiment. As a result, the low-cycle fatigue strength of the carburized steel parts decreases. Therefore, the sulfur content is 0.035% or less. The preferred upper limit for the sulfur content is 0.030%, more preferably 0.025%, even more preferably 0.020%, and even more preferably 0.015%. A low sulfur (S) content is preferable. However, excessive reduction of the S content increases manufacturing costs. Therefore, considering normal industrial production, the preferred lower limit of the S content is greater than 0%, more preferably 0.001%, more preferably 0.002%, more preferably 0.004%, and more preferably 0.007%.

[0046] Cr: 0.80~2.00% Chromium (Cr) enhances the hardenability of steel. As a result, the low-cycle fatigue strength of carburized steel parts made from steel is increased. If the Cr content is less than 0.80%, the above effect cannot be fully obtained, even if the content of other elements is within the range of this embodiment. On the other hand, if the Cr content exceeds 2.00%, the hardness of the steel becomes excessively high, even if the content of other elements is within the range of this embodiment. As a result, the machinability of the steel decreases. Therefore, the Cr content is 0.80-2.00%. The preferred lower limit for the Cr content is 0.90%, more preferably 1.00%, and even more preferably 1.10%. The preferred upper limit for the Cr content is 1.80%, more preferably 1.60%, and even more preferably 1.40%.

[0047] Al: 0.010~0.050% Aluminum (Al) deoxidizes steel. If the Al content is less than 0.010%, the above effect cannot be fully obtained, even if the content of other elements is within the range of this embodiment. On the other hand, if the Al content exceeds 0.050%, coarse oxide inclusions will form even if the content of other elements is within the range of this embodiment. These coarse oxide inclusions become the starting point for fatigue fracture. As a result, the low-cycle fatigue strength of carburized steel parts made from steel decreases. Therefore, the Al content is 0.010-0.050%. The preferred lower limit for the Al content is 0.015%, more preferably 0.018%, and even more preferably 0.020%. The preferred upper limit for the Al content is 0.048%, more preferably 0.045%, even more preferably 0.040%, and even more preferably 0.034%. In this specification, the Al content refers to the total Al content.

[0048] N: 0.0020~0.0200% Nitrogen (N) forms nitrides and carbonitrides, suppressing the coarsening of austenite grains. This refines the ferrite grains. As a result, the low-cycle fatigue strength of carburized steel parts made from steel is increased. N further enhances the low-cycle fatigue strength of carburized steel parts through solid solution strengthening. If the N content is less than 0.0020%, the above effects cannot be fully obtained, even if the content of other elements is within the range of this embodiment. On the other hand, if the N content exceeds 0.0200%, the nitrides and carbonitrides will coarseen, even if the content of other elements is within the range of this embodiment. In this case, the hot workability of the steel material will decrease. Therefore, the N content is between 0.0020% and 0.0200%. The preferred lower limit of the N content is 0.0030%, more preferably 0.0035%, even more preferably 0.0040%, even more preferably 0.0050%, and even more preferably 0.0090%. The preferred upper limit for the N content is 0.0180%, more preferably 0.0170%, and even more preferably 0.0160%.

[0049] Mo: 0.10~0.35% Molybdenum (Mo) enhances the hardenability of steel. As a result, the low-cycle fatigue strength of carburized steel parts made from steel is increased. If the Mo content is less than 0.10%, the above effect cannot be fully obtained, even if the content of other elements is within the range of this embodiment. On the other hand, if the Mo content exceeds 0.35%, the hardness of the steel becomes excessively high, even if the content of other elements is within the range of this embodiment. As a result, the machinability of the steel decreases. Therefore, the Mo content is 0.10-0.35%. The preferred lower limit for the Mo content is 0.12%, more preferably 0.14%, and even more preferably 0.15%. The preferred upper limit for the Mo content is 0.30%, more preferably 0.28%, and even more preferably 0.25%.

[0050] The remainder of the chemical composition of the steel material according to this embodiment consists of Fe and impurities. Here, impurities refer to substances that are mixed in from raw materials such as ore, scrap, or the manufacturing environment during the industrial production of steel material, and are acceptable within a range that does not adversely affect the steel material according to this embodiment.

[0051] [About Optional Elements] The chemical composition of the steel material in this embodiment may further contain one or more elements selected from the groups consisting of Group 1 and Group 2, in place of a portion of Fe. [Group 1] Cu: 0.40% or less, Ni: 0.30% or less, Mg: 0.0050% or less, V: 0.50% or less, Nb: 0.050% or less, Ti: 0.050% or less, Ca: 0.0020% or less, B: Select one or more from the group consisting of 0.0040% or less. [Group 2] Bi: 0.020% or less, Pb: 0.060% or less, Sn: 0.100% or less, Sb: 0.050% or less, and, One or more selected from the group consisting of As: 0.050% or less.

[0052] [Group 1: Cu, Ni, Mg, V, Nb, Ti, Ca and B] The chemical composition of the steel material in this embodiment may further contain one or more elements selected from the group consisting of Cu, Ni, Mg, V, Nb, Ti, Ca, and B in place of a portion of Fe. These elements are arbitrary and all enhance the low-cycle fatigue strength of carburized steel parts made from steel.

[0053] Cu: 0.40% or less Copper (Cu) is an optional element and does not need to be included. In other words, the Cu content may be 0%. When present, i.e., when the Cu content is greater than 0%, Cu enhances the hardenability of the steel. As a result, the low-cycle fatigue strength of carburized steel parts increases. Even a small amount of Cu content will provide some degree of the above effect. However, if the copper content exceeds 0.40%, the hardness of the steel increases excessively. As a result, the machinability of the steel decreases. Therefore, the Cu content is 0-0.40%, and if present, it is 0.40% or less. The preferred lower limit for the Cu content is 0.01%, more preferably 0.03%, and even more preferably 0.05%. The preferred upper limit for the Cu content is 0.38%, more preferably 0.35%, and even more preferably 0.33%.

[0054] Ni: 0.30% or less Nickel (Ni) is an optional element and does not need to be included. In other words, the Ni content may be 0%. When present, i.e., when the Ni content is greater than 0%, Ni enhances the hardenability of the steel. As a result, the low-cycle fatigue strength of carburized steel parts increases. Even a small amount of Ni content will provide some degree of the above effect. However, if the nickel content exceeds 0.30%, the hardness of the steel increases excessively. As a result, the machinability of the steel decreases. Therefore, the Ni content is 0-0.30%, and if present, it is 0.30% or less. The preferred lower limit for the Ni content is 0.01%, more preferably 0.03%, and even more preferably 0.05%. The preferred upper limit for the Ni content is 0.28%, more preferably 0.25%, and even more preferably 0.22%.

[0055] Mg: 0.0050% or less Magnesium (Mg) is an optional element and does not need to be included. In other words, the Mg content may be 0%. When Mg is present, that is, when the Mg content is greater than 0%, Mg modifies the sulfides in the steel. Therefore, it suppresses the elongation of sulfides during hot working in the steel manufacturing process. As a result, the low-cycle fatigue strength of carburized steel parts increases. Even if only a small amount of Mg is present, the above effect can be obtained to some extent. However, the above effect saturates when the Mg content exceeds 0.0050%. Therefore, the Mg content is between 0 and 0.0050%, and if present, it is 0.0050% or less. The preferred lower limit of the Mg content is 0.0001%, more preferably 0.0003%, and even more preferably 0.0005%. The preferred upper limit for the Mg content is 0.0048%, more preferably 0.0045%, and even more preferably 0.0043%.

[0056] V: 0.50% or less Vanadium (V) is an optional element and may not be present. In other words, the V content may be 0%. When V is present, that is, when the V content is greater than 0%, V combines with C and / or N in the steel to form fine V carbides, etc. These fine V carbides, etc., enhance the low-cycle fatigue strength of carburized steel parts through precipitation strengthening. Furthermore, these fine V carbides, etc., suppress the coarsening of austenite grains. As a result, the ferrite grains become finer. Consequently, the low-cycle fatigue strength of carburized steel parts increases. Even if only a small amount of V is present, the above effects can be obtained to some extent. However, if the V content exceeds 0.50%, even if the content of other elements is within the range of this embodiment, the V carbides and the like will become coarser. As a result, the low-cycle fatigue strength of the carburized steel parts will decrease. Therefore, the V content is 0-0.50%, and if present, it is 0.50% or less. The preferred lower limit of the V content is 0.01%, more preferably 0.05%, even more preferably 0.10%, and even more preferably 0.15%. The preferred upper limit for the V content is 0.45%, more preferably 0.40%, and even more preferably 0.35%.

[0057] Nb: 0.050% or less Niobium (Nb) is an optional element and may not be present. In other words, the Nb content may be 0%. When Nb is present, i.e., when the Nb content is greater than 0%, Nb combines with C and / or N in the steel to form fine Nb carbides, etc. These fine Nb carbides, etc., enhance the low-cycle fatigue strength of carburized steel parts through precipitation strengthening. Furthermore, these fine Nb carbides, etc., suppress the coarsening of austenite grains. As a result, the ferrite grains become finer. Consequently, the low-cycle fatigue strength of carburized steel parts increases. Even if only a small amount of Nb is present, the above effects can be obtained to some extent. However, if the Nb content exceeds 0.050%, even if the content of other elements is within the range of this embodiment, Nb carbides and the like will become coarser. As a result, the low-cycle fatigue strength of the carburized steel parts will decrease. Therefore, the Nb content is 0-0.050%, and if present, it is 0.050% or less. The preferred lower limit of the Nb content is 0.001%, more preferably 0.002%, and even more preferably 0.003%. The preferred upper limit for the Nb content is 0.040%, more preferably 0.035%, and even more preferably 0.030%.

[0058] Ti: 0.050% or less Titanium (Ti) is an optional element and does not need to be included. In other words, the Ti content may be 0%. When Ti is present, i.e., when the Ti content is greater than 0%, Ti combines with C and / or N in the steel to form fine Ti carbides, etc. These fine Ti carbides, etc., enhance the low-cycle fatigue strength of carburized steel parts through precipitation strengthening. Furthermore, these fine Ti carbides, etc., suppress the coarsening of austenite grains. As a result, the ferrite grains become finer. Consequently, the low-cycle fatigue strength of carburized steel parts increases. Even if only a small amount of Ti is present, the above effects can be obtained to some extent. However, if the Ti content exceeds 0.050%, even if the content of other elements is within the range of this embodiment, the Ti carbides and the like will become coarser. As a result, the low-cycle fatigue strength of the carburized steel parts will decrease. Therefore, the Ti content is 0-0.050%, and if present, it is 0.050% or less. The preferred lower limit for the Ti content is 0.001%, more preferably 0.002%, and even more preferably 0.003%. The preferred upper limit for the Ti content is 0.040%, more preferably 0.035%, and even more preferably 0.030%.

[0059] Ca:0.0020% or less Calcium (Ca) is an optional element and does not need to be included. In other words, the Ca content may be 0%. When calcium is present, i.e., when the calcium content is greater than 0%, calcium modifies the sulfides in the steel. Therefore, it suppresses the elongation of sulfides during hot working in the steel manufacturing process. As a result, the low-cycle fatigue strength of carburized steel parts increases. Even a small amount of calcium can provide some degree of this effect. However, the above effect saturates when the Ca content exceeds 0.0020%. Therefore, the Ca content is 0-0.0020%, and if present, it is 0.0020% or less. The preferred lower limit for the Ca content is 0.0001%, more preferably 0.0003%, and even more preferably 0.0005%. The preferred upper limit for the Ca content is 0.0018%, more preferably 0.0015%, and even more preferably 0.0013%.

[0060] B: 0.0040% or less Boron (B) is an optional element and does not need to be included. In other words, the B content may be 0%. When present, i.e., when the B content is greater than 0%, B enhances the hardenability of the steel. As a result, the low-cycle fatigue strength of carburized steel parts increases. Even a small amount of B present will provide some degree of the above effect. However, if the B content exceeds 0.0040%, the above effect will saturate. Therefore, the B content is between 0 and 0.0040%, and if present, it is 0.0040% or less. The preferred lower limit for the B content is 0.0001%, more preferably 0.0003%, and even more preferably 0.0005%. The preferred upper limit for the B content is 0.0038%, more preferably 0.0035%, and even more preferably 0.0033%.

[0061] [Group 2: Bi, Pb, Sn, Sb, and As] The chemical composition of the steel material in this embodiment may further contain one or more elements selected from the group consisting of Bi, Pb, Sn, Sb, and As, in place of a portion of Fe. These elements are arbitrary and all enhance the machinability of the steel material.

[0062] Bi:0.020% or less Bismuth (Bi) is an optional element and does not need to be included. In other words, the Bi content may be 0%. When present, i.e., when the Bi content is greater than 0%, Bi improves the machinability of steel. Even a small amount of Bi will provide some degree of the above effect. However, if the Bi content exceeds 0.020%, the hot workability of the steel material decreases. Therefore, the Bi content is 0-0.020%, and if present, it is 0.020% or less. The preferred lower limit of the Bi content is 0.001%, more preferably 0.003%, and even more preferably 0.005%. The preferred upper limit for the Bi content is 0.018%, more preferably 0.015%, and even more preferably 0.013%.

[0063] Pb:0.060% or less Lead (Pb) is an optional element and does not need to be included. In other words, the Pb content may be 0%. When Pb is present, that is, when the Pb content is greater than 0%, Pb improves the machinability of steel. Even if only a small amount of Pb is present, the above effect can be obtained to some extent. However, if the Pb content exceeds 0.060%, the hot workability of the steel decreases. Therefore, the Pb content is between 0 and 0.060%, and if present, it is 0.060% or less. The preferred lower limit of the Pb content is 0.001%, more preferably 0.005%, even more preferably 0.010%, and even more preferably 0.015%. The preferred upper limit for the Pb content is 0.050%, more preferably 0.045%, and even more preferably 0.040%.

[0064] Sn: 0.100% or less Tin (Sn) is an optional element and does not need to be included. In other words, the Sn content may be 0%. When present, i.e., when the Sn content is greater than 0%, Sn improves the machinability of steel. Even a small amount of Sn present will provide some degree of the above effect. However, if the Sn content exceeds 0.100%, the hot workability of the steel decreases. Therefore, the Sn content is between 0 and 0.100%, and if present, it is less than 0.100%. The preferred lower limit for the Sn content is 0.001%, more preferably 0.005%, and even more preferably 0.010%. The preferred upper limit for the Sn content is 0.095%, more preferably 0.090%, and even more preferably 0.085%.

[0065] Sb: 0.050% or less Antimony (Sb) is an optional element and does not need to be included. In other words, the Sb content may be 0%. When present, i.e., when the Sb content is greater than 0%, Sb improves the machinability of steel. Even a small amount of Sb will provide some degree of the above effect. However, if the Sb content exceeds 0.050%, the hot workability of the steel decreases. Therefore, the Sb content is 0-0.050%, and if present, it is 0.050% or less. The preferred lower limit of the Sb content is 0.001%, more preferably 0.005%, more preferably 0.008%, and still more preferably 0.010%. The preferred upper limit for the Sb content is 0.040%, more preferably 0.030%, and even more preferably 0.026%.

[0066] As: 0.050% or less Arsenic (As) is an optional element and does not need to be included. In other words, the As content may be 0%. When present, i.e., when the as content is greater than 0%, as improves the machinability of steel. Even a small amount of as will provide some degree of the above effect. However, if the As content exceeds 0.050%, the hot workability of the steel material decreases. Therefore, the As content is between 0 and 0.050%, and if present, it is 0.050% or less. The preferred lower limit for the As content is 0.001%, more preferably 0.005%, more preferably 0.008%, and still more preferably 0.010%. The preferred upper limit for the As content is 0.040%, more preferably 0.030%, and even more preferably 0.027%.

[0067] [Regarding (Feature 2) Equation (1)] The steel material of this embodiment further satisfies equation (1). 3.5≦(8Mn+3Cr) / (Si+5Mo)≦6.8 (1) Here, each element symbol in equation (1) is substituted with the mass percentage of the corresponding element's content in the chemical composition.

[0068] As described above, F1 is defined as F1 = (8Mn + 3Cr) / (Si + 5Mo). If F1 satisfies equation (1) above, the low-cycle fatigue strength of the carburized steel part will increase. The reason for this is not entirely clear, but the following reasons are possible. Mn and Cr are elements that affect the coarsening of pearlite grains (hereinafter referred to as pearlite coarsening contributing elements). Si and Mo are elements that affect the coarsening of ferrite grains (hereinafter referred to as ferrite coarsening contributing elements). If F1 is less than 3.5, even if the chemical composition of the steel material according to this embodiment satisfies feature 1, the contribution of the ferrite coarsening contributing elements is greater than that of the pearlite coarsening contributing elements. In this case, the ferrite grains become coarser, while the pearlite grains become finer. Therefore, in the microstructure of the quenched layer, the prior austenite grains become coarser, and the variation in the size of the prior austenite grains increases. As a result, the low-cycle fatigue strength of the carburized steel part does not increase sufficiently. On the other hand, if F1 exceeds 6.8, even if the chemical composition of the steel material according to this embodiment satisfies Feature 1, the contribution of pearlite coarsening elements is greater than that of ferrite coarsening elements. In this case, pearlite grains become coarser, while ferrite grains become finer. Therefore, in the microstructure of the quenched layer, prior austenite grains become coarser, and the variation in the size of prior austenite grains increases. As a result, the low-cycle fatigue strength of the carburized steel parts does not increase sufficiently.

[0069] If F1 is between 3.5 and 6.8, assuming the chemical composition of the steel satisfies Feature 1, both ferrite and pearlite grains in the steel will be of appropriate size. Furthermore, variations between the prior austenite grains in the region where ferrite grains transformed into austenite during heating for carburizing and became martensite due to quenching, and the prior austenite grains in the region where pearlite grains transformed into austenite during heating for carburizing and became martensite due to quenching, are suppressed. As a result, in the microstructure of the quenched layer formed on the surface of the carburized part, the coarsening of prior austenite grains is suppressed, and variations in the size of prior austenite grains are also suppressed. Consequently, assuming the steel satisfies Feature 1, Feature 3, and Feature 4, the low-cycle fatigue strength of the carburized steel part is increased.

[0070] It should be noted that a mechanism other than the one described above may also be at work. However, the fact that low-cycle fatigue strength increases when F1 satisfies equation (1) above has been demonstrated in the examples described later.

[0071] The preferred lower limit of F1 is 3.8, more preferably 4.0, and even more preferably 4.3. The preferred upper limit of F1 is 6.5, more preferably 6.3, and even more preferably 6.0. The value of F1 is the first decimal place obtained by rounding to the second decimal place.

[0072] [(Feature 3) About Microorganisms] In the steel material of this embodiment, the microstructure further consists of ferrite area ratio of 50-70%, bainite area ratio of 20% or less, and the remainder consisting of pearlite. The following explains the area ratios of ferrite and bainite.

[0073] [Regarding the area ratio of ferrite] In the microstructure of the steel material according to this embodiment, the area ratio of ferrite is 50-70%. If the area ratio of ferrite is 50-70%, assuming that the steel material satisfies features 1, 2, and 4, and that the area ratio of bainite in the steel material is 20% or less, with the remainder being pearlite, the low-cycle fatigue strength of the carburized steel parts will increase.

[0074] Even if the steel material satisfies features 1, 2, and 4, if the ferrite area ratio is less than 50%, the pearlite area ratio in the steel material's microstructure becomes too high. As a result, the size of the prior austenite grains in the quenched layer formed on the surface of the steel material after carburizing treatment varies. Consequently, the low-cycle fatigue strength of the carburized steel part decreases. Even if the steel material satisfies features 1, 2, and 4, if the ferrite area ratio exceeds 70%, the pearlite area ratio in the steel material's microstructure becomes too low. As a result, the size of the prior austenite grains in the quenched layer formed on the surface of the part after carburizing treatment varies. Consequently, the low-cycle fatigue strength of the carburized steel part decreases. Therefore, the ferrite area ratio is 50-70%. The preferred lower limit for the ferrite area ratio is 52%, more preferably 55%, and still more preferably 57%. The preferred upper limit for the ferrite area ratio is 68%, more preferably 65%, and still more preferably 63%.

[0075] [Regarding the area ratio of bainite] In the microstructure of the steel material according to this embodiment, the area ratio of bainite is 20% or less. Assuming that the steel material satisfies features 1, 2, and 4, and that the ferrite area ratio of the steel material is 50-70% and the remainder is pearlite, the low-cycle fatigue strength of the carburized steel parts is increased.

[0076] Even if the steel material satisfies features 1, 2, and 4, if the bainite area ratio exceeds 20%, the size of the prior austenite grains in the quenched layer formed on the surface of the steel material after carburizing treatment tends to vary. As a result, the low-cycle fatigue strength of the carburized steel parts does not increase sufficiently. Therefore, the bainite area ratio should be 20% or less. The preferred upper limit for the bainite area ratio is 18%, more preferably 15%, and even more preferably 13%.

[0077] Furthermore, a lower bainite area ratio is preferable. However, excessive reduction of the bainite area ratio increases manufacturing costs. Therefore, considering normal industrial production, the preferable lower limit for bainite is greater than 0%. The preferable lower limit for the bainite area ratio may be 2% or 4%.

[0078] [Method for measuring the area ratio of ferrite and bainite] The area ratios of ferrite and bainite in the microstructure of the steel material according to this embodiment are measured by the following method. If the steel material is a bar or wire, a sample is taken from the midpoint of the radius R connecting the surface and the central axis (R / 2 position) of the cross section (hereinafter referred to as the transverse surface) perpendicular to the longitudinal direction (axial direction) of the steel material. Of the surface of the collected sample, the surface corresponding to the above transverse surface is used as the observation surface. After mirror polishing the observation surface, the observation surface is etched using 2% nitric acid alcohol (Nital etching solution). The etching time is 30 seconds. The etched observation surface is observed at a magnification of 1000x using an optical microscope, and 20 field-of-view photographic images are generated at the R / 2 position. The size of each field of view is 131 μm vertically × 167 μm horizontally.

[0079] In each field of view, the ferrite, pearlite, and bainite structures can be distinguished by contrast. Figure 1 is a magnified optical microscope image showing ferrite and pearlite in the microstructure of the steel material of this embodiment. Figure 2 is a magnified optical microscope image showing ferrite and bainite in the microstructure of the steel material of this embodiment. Referring to Figure 1, the bright white or light gray structure (phase) is identified as ferrite 1. There are no areas of varying light and dark within the ferrite 1 grains, and the lightness is almost uniform. On the other hand, the structure that is less bright than ferrite 1 and closer to black in color is identified as pearlite 2. Typically, there are areas of varying light and dark within the pearlite 2 grains, and the lightness within the grains is not uniform.

[0080] Furthermore, referring to Figure 2, we identify the dark gray structure, whose brightness is higher than pearlite 2 in Figure 1 but lower than ferrite 1, as bainite 3. Similar to pearlite 2, bainite 3 typically has areas of varying brightness within the grains, and the brightness within the grains is not uniform. As described above, the brightness of the structures decreases in the order of ferrite 1, bainite 3, and pearlite 2. Therefore, the structures (ferrite, pearlite, and bainite) can be distinguished based on contrast.

[0081] For each identified tissue, the area of ​​ferrite 1 in each field of view was determined using WinROOF, image analysis and measurement software manufactured by Mitani Corporation, for each photographic image of the field of view obtained by optical microscopy. 2 ), and the area of ​​bainite 3 (μm²) 2 Calculate the area (μm²) of ferrite 1 in each field of view. 2 ), and the area of ​​bainite 3 (μm²) 2 Based on this, the total area of ​​ferrite 1 in all fields of view (μm 2 ), and the total area of ​​bainite 3 (μm²) 2The area ratio of ferrite is defined as the ratio (%) of the total area of ​​ferrite 1 in all fields of view to the total area of ​​all fields of view. The area ratio of bainite is defined as the ratio (%) of the total area of ​​bainite 3 in all fields of view to the total area of ​​all fields of view. The area ratios of ferrite and bainite are integer values ​​obtained by rounding to the first decimal place.

[0082] [(Feature 4) Regarding ferrite crystal grains] In the steel material of this embodiment, the average equivalent circle diameter of the ferrite grains (hereinafter also referred to as the average ferrite grain size) in the microstructure is 40 μm or less, and the standard deviation of the equivalent circle diameter of the ferrite grains (hereinafter also referred to as the standard deviation of the ferrite grain size) is 10 μm or less.

[0083] If the average ferrite particle size is 40 μm or less and the standard deviation of the ferrite particle size is 10 μm or less, then, assuming that the steel material satisfies characteristics 1 to 3, the low-cycle fatigue strength of a carburized steel part will increase after being subjected to carburizing treatment.

[0084] Even if the steel material satisfies characteristics 1 to 3, if the average ferrite grain size exceeds 40 μm, the ferrite and pearlite grains of the steel material are not sufficiently refined. Therefore, when carburizing treatment is applied, the prior austenite grains of the quenched layer formed on the surface of the part tend to coarseen. As a result, the low-cycle fatigue strength of the carburized steel part does not increase sufficiently. For this reason, the average ferrite grain size should be 40 μm or less. The preferred upper limit for the average ferrite grain size is 38 μm, more preferably 35 μm, and even more preferably 30 μm.

[0085] Furthermore, a smaller average ferrite particle size is preferable. However, excessive reduction of the average ferrite particle size increases the burden on equipment such as rolling mills. Therefore, considering normal industrial production, the lower limit of the average ferrite particle size is 15 μm. A preferred lower limit for the average ferrite particle size may be 20 μm or 25 μm.

[0086] Even if the steel material satisfies characteristics 1 to 3, if the standard deviation of the ferrite grain size exceeds 10 μm, the variation in the microstructure size of the steel material is not sufficiently suppressed. As a result, when carburizing treatment is applied, the variation in the size of the prior austenite grains in the quenched layer formed on the surface of the part becomes large. Consequently, the low-cycle fatigue strength of the carburized steel part does not increase sufficiently. Therefore, the standard deviation of the ferrite grain size should be 10 μm or less. The preferred upper limit for the standard deviation of the ferrite grain size is 9 μm, more preferably 8 μm, and even more preferably 7 μm.

[0087] Furthermore, a smaller standard deviation in ferrite particle size is preferable. However, excessive reduction in the standard deviation of ferrite particle size increases the burden on equipment such as rolling mills. Therefore, considering normal industrial production, the lower limit of the standard deviation of ferrite particle size is 3 μm. A preferred lower limit for ferrite particle size may be 4 μm or 5 μm.

[0088] [Method for measuring the average particle size and standard deviation of ferrite particle size] The average ferrite grain size and the standard deviation of ferrite grain size in the microstructure of the steel material according to this embodiment are measured by the following method. If the steel material is a bar or wire, a sample is taken from the center position (R / 2 position) of the radius R connecting the surface of the steel material and the central axis, in a cross section (hereinafter referred to as the transverse surface) perpendicular to the longitudinal direction (axial direction) of the steel material. The transverse surface of the collected sample is used as the observation surface. After mirror polishing the observation surface, the observation surface is etched using 2% nitric acid alcohol (Nital etching solution). The etched observation surface is observed at a magnification of 1000x using an optical microscope, and photographic images are generated at 20 observation fields at the R / 2 position. The size of each observation field is 131 μm vertically × 167 μm horizontally.

[0089] As described in the above-mentioned [Method for measuring the area fraction of ferrite and bainite], ferrite has a different contrast from pearlite and bainite in each observation field. Specifically, regions with a brighter contrast than pearlite and bainite are identified as ferrite. For the photographic image in each observation field, the area S (μm²) of the identified ferrite grains is calculated. 2 The area of ​​each ferrite grain is measured using WinROOF, an image analysis and measurement software manufactured by Mitani Corporation. Note that ferrite grains where the grain boundary is interrupted at the edge of the observation field are also included in the area S of the ferrite grain. Based on the measured area S of each ferrite grain, the equivalent circular diameter D (μm) of each ferrite is determined. D = (4S / 3.14) 1 / 2 The arithmetic mean of the equivalent circle diameter D of each ferrite particle in the entire field of view is defined as the average ferrite particle size (μm). Note that the area S is 14 μm when calculating the equivalent circle diameter D. 2 The ferrite grains described above will be used for measurement of the equivalent circle diameter D. Furthermore, the total number of ferrite grains to be measured will be 400 or more. If the total number of ferrite grains is less than 400, an additional field of view will be added to ensure that the total number of ferrite grains is 400 or more. In this case, the field of view will be at the R / 2 position of the steel material, as described above. The average ferrite grain size is an integer value obtained by rounding to the first decimal place.

[0090] Furthermore, the standard deviation (μm) of the ferrite particle size is determined based on the equivalent circular diameter D of each ferrite and the average ferrite particle size obtained above. The standard deviation referred to here is the sample standard deviation. The standard deviation of the ferrite particle size is an integer value obtained by rounding to the first decimal place.

[0091] [Effects of the steel material in this embodiment] The steel material of this embodiment satisfies features 1 to 4. Therefore, when the steel material of this embodiment is subjected to carburizing treatment to become a carburized steel part, it exhibits excellent low-cycle fatigue strength.

[0092] [Regarding the applications of the steel material of this embodiment] As described above, the steel material according to this embodiment is suitable as a material for carburized steel parts. In particular, the steel material according to this embodiment is suitable for gears used in automobile differential gears, etc. It is also possible to use the steel material according to this embodiment for carburized steel parts for other applications besides differential gears.

[0093] [Method for manufacturing steel material according to this embodiment] An example of a method for manufacturing steel according to this embodiment will be described. The method for manufacturing steel described below is just one example for manufacturing steel according to this embodiment. Therefore, steel having the above-described configuration may be manufactured by other manufacturing methods other than the method described below. However, the manufacturing method described below is a preferred example of a method for manufacturing steel according to this embodiment.

[0094] An example of a steel manufacturing method according to this embodiment comprises a step of preparing the material (material preparation step) and a step of manufacturing the steel by hot working the material (hot working step). Each step will be described below.

[0095] [Material preparation process] A material having the above-described chemical composition is prepared. Specifically, molten steel whose chemical composition satisfies characteristics 1 and 2 is produced. The refining method is not particularly limited, and any well-known method may be used. For example, molten iron produced by a well-known method is refined in a converter (primary refining). A well-known secondary refining is performed on the molten steel tapped from the converter. In the secondary refining, alloying elements for composition adjustment are added to produce molten steel whose chemical composition satisfies characteristics 1 and 2.

[0096] Using the molten steel produced by the refining method described above, a material is manufactured by a well-known casting method. For example, a billet is manufactured using molten steel by a continuous casting method. Alternatively, an ingot may be manufactured using molten steel by a bloc-making method. If an ingot is manufactured, a billet may be manufactured by bloc rolling using a bloc rolling mill. A billet is manufactured by the above method.

[0097] [Hot working process] Steel materials are manufactured by performing hot working on prepared billets. When hot rolling is performed as the hot working, for example, the following steps are carried out. Hot rolling includes a rough rolling step in which the billet is roughly rolled, and a finish rolling step in which the roughly rolled steel material is finish rolled.

[0098] [Rough rolling process] The rough rolling process involves, for example, the following steps: After heating the billet, it is roughly rolled using a continuous rough rolling mill. In a continuous rough rolling mill, horizontal roll stands and vertical roll stands are arranged alternately in a row, and the billet is rolled using the holes formed in the rolling rolls of each stand.

[0099] [Finishing Rolling Process] The finishing rolling process involves, for example, the following steps: The roughly rolled steel is continuously finished (hot rolled) in a series of finishing mills to produce steel of a predetermined diameter. The series of finishing mills includes multiple stands arranged in a row. Each stand includes multiple rolls arranged around a pass line. The roughly rolled steel is finished using the holes formed in the rolling rolls of each stand to produce steel (bars / wires) of a predetermined diameter.

[0100] Furthermore, the hot working process is not limited to hot rolling. Instead of the hot rolling described above, hot forging or hot extrusion may be performed in the hot working process.

[0101] [Regarding heating temperature] In the hot working process, the heating temperature of the steel material is not particularly limited. For example, if the hot working process includes a rough rolling process and a finish rolling process, the heating temperature in the furnace during the rough rolling process is 1000 to 1300°C, and the finish rolling temperature during the finish rolling process is 800 to 950°C. The "finish rolling temperature" (°C) is defined as the surface temperature of the steel material at the exit of the final rolling stand in the finish rolling mill train.

[0102] The steel material of this embodiment is manufactured through the above manufacturing process.

[0103] [Regarding manufacturing conditions] The above manufacturing method satisfies the following conditions 1 to 3. (Condition 1) The reduction ratio F in the final hot working is 15% or more. (Condition 2) The cooling rate V of the steel material after hot working is 0.20 to 1.00 °C / second. (Condition 3) In the hot working process, F2, defined by the following equation (2), becomes 0.60 or greater. F2 = F / 100 + V (2) In equation (2), F is the reduction ratio (%) during the final hot working, and V is the cooling rate (°C / sec) after hot working. Conditions 1 through 3 are explained below.

[0104] [Regarding Condition 1] In a hot working process, the reduction in cross-sectional area (area reduction ratio) F in the final hot working stage is 15% or more. For example, if the hot working process includes a rough rolling stage and a finish rolling stage, the reduction in cross-sectional area in the finish rolling stage, specifically the last four stands of the finish rolling mill train, is defined as the area reduction ratio F in the final hot working stage. Here, if the hot working process includes a rough rolling stage and a finish rolling stage, the area reduction ratio F in the finish rolling stage is defined by the following formula. Area reduction ratio F = (Cross-sectional area just before passing the 3rd stand before the final stand of the finishing rolling train - Cross-sectional area just after passing the final stand of the finishing rolling train) / Cross-sectional area just before passing the 3rd stand before the final stand of the finishing rolling train × 100

[0105] If the reduction ratio F is less than 15%, the average ferrite grain size of the steel exceeds 40 μm. If the reduction ratio F is 15% or more, assuming conditions 2 and 3 are met, the average ferrite grain size in the microstructure of the steel will be 40 μm or less. A higher reduction ratio F is preferable. However, if the reduction ratio F is excessively high, manufacturing costs will increase. Therefore, considering normal industrial production, the reduction ratio F is 40% or less.

[0106] [Regarding Condition 2] The cooling rate V of steel after hot working is between 0.20 and 1.00°C / second. Here, the cooling rate V after hot working is defined as follows: After the completion of hot working, the average cooling rate from 800°C to 500°C of the steel surface is defined as the cooling rate V (°C / second) after hot working. If the cooling rate V after hot working is less than 0.20°C / second, the area ratio of ferrite in the microstructure of the steel exceeds 70%. Furthermore, if the cooling rate V after hot working is less than 0.20°C / second, the average ferrite grain size of the steel may exceed 40 μm. On the other hand, if the cooling rate V after hot working exceeds 1.00°C / second, the area ratio of bainite in the microstructure of the steel exceeds 20%.

[0107] Assuming that conditions 1 and 3 are met, if the cooling rate V of the steel after hot working is 0.20 to 1.00 °C / second, the area ratio of ferrite in the microstructure of the steel will be 50% to 70%, the area ratio of bainite will be 20% or less, and the remainder will consist of pearlite. Furthermore, the average grain size of ferrite will be 40 μm or less.

[0108] [Regarding Condition 3] In the hot working process, F2, defined by the following equation (2), is further set to 0.60 or higher. F2 = F / 100 + V (2) In equation (2), F is the reduction ratio (%) during the final hot working, and V is the cooling rate (°C / sec) of the steel after hot working.

[0109] As mentioned above, if the average ferrite grain size of the steel is 40 μm or less, the coarsening of the prior austenite grains in the quenched layer formed on the surface of the part after carburizing is suppressed. As a result, the low-cycle fatigue strength of the carburized steel part increases. However, even if the average ferrite grain size of the steel is 40 μm or less, if the standard deviation of the ferrite grain size exceeds 10 μm, the variation in the size of the microstructure of the steel is too large. Therefore, the variation in the size of the prior austenite grains in the quenched layer formed on the surface of the part after carburizing becomes large. As a result, the low-cycle fatigue strength of the carburized steel part does not increase sufficiently.

[0110] To keep the standard deviation of ferrite grain size in steel materials below 10 μm, it is effective to increase the reduction ratio F during the final hot working stage. However, the standard deviation of ferrite grain size in steel materials is affected not only by the reduction ratio F during the hot working stage but also by the cooling rate V after hot working. Therefore, to keep the standard deviation of ferrite grain size in steel materials below 10 μm, it is effective to appropriately control the balance between the reduction ratio F and the cooling rate V. Specifically, when the reduction ratio F is low, as mentioned above, the ferrite grains in the steel material tend to coarseen. Furthermore, when the cooling rate V after hot working is slow, the ferrite transformation begins at a high temperature in the steel material. Therefore, the ferrite grains in the steel material tend to coarseen. Consequently, even if conditions 1 and 2 above are met, if F2 is less than 0.60, some ferrite grains tend to coarseen. As a result, the standard deviation of ferrite grain size may exceed 10 μm.

[0111] If F2 is less than 0.60, the standard deviation of the ferrite grain size of the steel material may exceed 10 μm, even if conditions 1 and 2 are met. If F2 is 0.60 or higher, assuming conditions 1 and 2 are met, the standard deviation of the ferrite grain size will be 10 μm or less.

[0112] The preferred lower limit of F2 is 0.65, and more preferably 0.70. The upper limit of F2 is not particularly limited. However, as long as the above-mentioned ranges of reduction ratio F and cooling rate V are met, the upper limit of F2 is 1.40 or less.

[0113] By fulfilling the above manufacturing process and conditions, steel materials satisfying features 1 to 4 are produced. Note that steel materials satisfying features 1 to 4 may also be produced by manufacturing methods other than those described above.

[0114] [Regarding carburized steel parts] Carburized steel parts made from the steel material of this embodiment can be manufactured, for example, by the following manufacturing method.

[0115] An example of a manufacturing method for carburized steel parts includes, for instance, a hot working process and / or a cutting process, and a carburizing process (carburizing, quenching, and tempering). Carburizing includes carbonitriding, and carburizing includes gas carburizing and vacuum carburizing. In the hot working process, the steel material of this embodiment is subjected to hot working to produce an intermediate product having a predetermined shape. The hot working is, for example, hot forging. In the hot working process, the steel material is A c3 The steel material is processed after being heated to a certain temperature. Therefore, the microstructure of the steel material is reset to some extent during the heating process of the hot working process. However, with the steel material of this embodiment, even if the hot working process is performed, the microstructure of the steel material is not completely reset by satisfying conditions 1 to 3 above, and the coarsening and size variation of the prior austenite grains in the quenched layer after carburizing and quenching is suppressed. Machining may be performed on the intermediate product after hot working. Alternatively, only the machining process may be performed instead of the hot working process. When only the machining process is performed, machining is performed on the steel material of this embodiment to produce an intermediate product having a predetermined shape. In this case, the intermediate product has a microstructure equivalent to that of the steel material.

[0116] Carburized steel parts are manufactured by performing a carburizing process on intermediate products after hot working or machining. The carburizing process includes carburizing quenching and tempering. In carburizing quenching, the intermediate product is subjected to A in an atmosphere containing a well-known carburizing modified gas. c3 After heating and holding above the transformation point, the material is rapidly cooled. In the tempering process, for example, a carburized and quenched intermediate product is held at a temperature range of 150 to 200°C for a predetermined time.

[0117] The steel material according to this embodiment will be described in more detail below with reference to examples. [Examples]

[0118] The effects of the steel material of this embodiment will be further explained in detail by the following examples. The conditions in the following examples are just one example of conditions adopted to confirm the feasibility and effects of the steel material of this embodiment. Therefore, the steel material of this embodiment is not limited to this one example of conditions.

[0119] Steel materials having the chemical compositions shown in Tables 1A and 1B were manufactured by the following method. In the following explanation, Tables 1A and 1B will be collectively referred to as "Table 1".

[0120] [Table 1A]

[0121] [Table 1B]

[0122] Steel bars with the chemical composition shown in Table 1 were manufactured by the following method. Specifically, billets were manufactured using the continuous casting method in the continuous casting process, using molten steel produced in the refining process. Hot working processes (rough rolling and finish rolling) were performed on the billets. In the rough rolling process, billets heated to a heating temperature of 1250°C were roughly rolled using a continuous rough rolling mill. In the finish rolling process, the roughly rolled steel was continuously finished rolled in a series of finish rolling mills. The finish rolling temperature was 860°C. In the finish rolling process, the reduction ratio F (%) in the final hot working, the cooling rate V (°C / sec) of the steel after hot working, and F2 are as shown in Table 2.

[0123] [Table 2]

[0124] [Evaluation Test] The following evaluation tests were conducted using the steel materials for each test number. (Test 1) Measurement test of ferrite area ratio and bainite area ratio (Test 2) Measurement test of average ferrite particle size and standard deviation of ferrite particle size (Test 3) Evaluation test of low-cycle fatigue strength The following describes each test.

[0125] [(Test 1) Measurement test of ferrite area ratio and bainite area ratio] Based on the method described in [Method for Measuring the Area Ratio of Ferrite and Bainite] above, the area ratio of ferrite and bainite was determined for each test number of steel material. The obtained area ratios of ferrite and bainite are shown in the "Ferrite Area Ratio (%)" and "Bainite Area Ratio (%)" columns of Table 2.

[0126] [(Test 2) Measurement test of average ferrite particle size and standard deviation of ferrite particle size] Based on the method described in [Method for Measuring Average Ferrite Particle Size and Standard Deviation of Ferrite Particle Size] above, the average ferrite particle size and standard deviation of ferrite particle size were determined for each test number of steel material. The obtained average ferrite particle size and standard deviation of ferrite particle size are shown in the "Average Ferrite Particle Size (μm)" column and the "Standard Deviation of Ferrite Particle Size (μm)" column in Table 2.

[0127] [(Test 3) Evaluation test of low-cycle fatigue strength] Low-cycle fatigue tests were conducted using the steel materials of each test number. Specifically, the steel materials of each test number were machined to obtain test specimens with the shape shown in Figure 3. Figure 3 shows the top, side, and front views of the test specimens used to measure the low-cycle fatigue strength. The numbers in Figure 3 indicate dimensions in mm. The test specimen was 17 mm high, 19 mm wide, and 100 mm long. The top and bottom surfaces of the test specimen had flat surfaces. Figure 4 is an enlarged view of the test section formed at the center of the length of the test specimen. The numbers in Figure 4 indicate dimensions in mm. The test section was formed perpendicular to the longitudinal direction of the test specimen (i.e., in the circumferential direction of the test specimen). The test section was 3 mm deep. The bottom of the notch in the test section was semicircular with a radius of curvature of 1.5 mm.

[0128] Vacuum carburizing and quenching was performed on each test specimen. During vacuum carburizing and quenching, the pressure inside the furnace was maintained at 10 Pa or less. The temperature during vacuum carburizing and quenching was 950°C, and the holding time during vacuum carburizing and quenching was 140 minutes. After vacuum carburizing and quenching, tempering was performed on the test specimens. The temperature during tempering was 180°C, and the holding time at the tempering temperature was 120 minutes. After tempering, a four-point bending low-cycle fatigue test was performed on the test specimens using an electro-hydraulic servo-type fatigue testing machine. The test specimens were placed in the electro-hydraulic servo-type fatigue testing machine so that the side with the flat portion was the bottom surface. The distance between the upper supports of the test specimen was 20 mm, and the distance between the lower supports was 80 mm. The stress ratio between the maximum load stress and the minimum load stress was 0.1. The frequency was 5 Hz. The fracture strength at 1000 stress load cycles was defined as the low-cycle fatigue strength (MPa). If the low-cycle fatigue strength is 1300 MPa or higher, it is judged to have superior low-cycle fatigue strength.

[0129] [Test Results] Referring to Tables 1 and 2, the steel materials in test numbers 1 to 35 met characteristics 1 to 4. Therefore, in the low-cycle fatigue tests conducted using the steel materials for each test number, the low-cycle fatigue strength was 1300 MPa or higher, indicating high low-cycle fatigue strength.

[0130] On the other hand, test number 36 had too low a carbon content. As a result, its low-cycle fatigue strength was less than 1300 MPa, indicating low low-cycle fatigue strength.

[0131] Test number 37 had too low a Si content. As a result, its low-cycle fatigue strength was less than 1300 MPa, indicating low low-cycle fatigue strength.

[0132] Test number 38 had too low a manganese content. As a result, its low-cycle fatigue strength was less than 1300 MPa, indicating low low-cycle fatigue strength.

[0133] Test number 39 had too high a phosphorus (P) content. As a result, its low-cycle fatigue strength was less than 1300 MPa, indicating low low-cycle fatigue strength.

[0134] Test number 40 had too high a sulfur content and too low an aluminum content. As a result, its low-cycle fatigue strength was less than 1300 MPa, indicating low low-cycle fatigue strength.

[0135] Tests 41 and 42 had too low a molybdenum content. As a result, the low-cycle fatigue strength was less than 1300 MPa, indicating low low-cycle fatigue strength.

[0136] Test numbers 43 and 44 showed an F1 value exceeding 6.8. In other words, F1 did not satisfy equation (1). As a result, the low-cycle fatigue strength was less than 1300 MPa, indicating low low-cycle fatigue strength.

[0137] Test numbers 45 and 46 had an F1 value of less than 3.5. In other words, F1 did not satisfy equation (1). Therefore, the average ferrite particle size was greater than 40 μm. As a result, the low-cycle fatigue strength was less than 1300 MPa, indicating low low-cycle fatigue strength.

[0138] In test numbers 47-49, the F2 value was less than 0.60 during the hot working process. As a result, the standard deviation of the ferrite grain size was greater than 10 μm. Consequently, the low-cycle fatigue strength was less than 1300 MPa, indicating low low-cycle fatigue strength.

[0139] In tests 50 and 51, the reduction ratio F was too low during the hot working process. As a result, the average ferrite particle size was over 40 μm. Consequently, the low-cycle fatigue strength was less than 1300 MPa, indicating low low-cycle fatigue strength.

[0140] In tests 52 and 53, the cooling rate V after hot working was too fast. As a result, the bainite area ratio exceeded 20%. Consequently, the low-cycle fatigue strength was less than 1300 MPa, indicating low low-cycle fatigue strength.

[0141] In test number 54, the cooling rate V after hot working was too slow. As a result, the ferrite area ratio exceeded 70%. Furthermore, the average ferrite particle size was over 40 μm. Consequently, the low-cycle fatigue strength was less than 1300 MPa, indicating low low-cycle fatigue strength.

[0142] In test number 55, although the reduction ratio F was sufficiently high during the hot working process, the cooling rate V after hot working was too slow. As a result, the ferrite area ratio exceeded 70%. Consequently, the low-cycle fatigue strength was less than 1300 MPa, indicating low low-cycle fatigue strength.

[0143] The embodiments of this disclosure have been described above. However, the embodiments described above are merely examples for implementing this disclosure. Therefore, this disclosure is not limited to the embodiments described above, and the embodiments described above can be modified as appropriate without departing from the spirit of this disclosure.

Claims

1. In mass percent, C: 0.10-0.30%, Si: 0.65-2.00%, Mn: 0.48-1.00%, P: 0.035% or less, S: 0.035% or less, Cr: 0.80-2.00%, Al: 0.010-0.050%, N: 0.0020 to 0.0200%, and, It contains Mo: 0.10-0.35%, The remainder consists of Fe and impurities. Satisfying equation (1), In the microstructure, the area ratio of ferrite is 50-70%, the area ratio of bainite is 20% or less, and the remainder consists of pearlite. The average circular equivalent diameter of the ferrite grains is 40 μm or less. The standard deviation of the equivalent circular diameter of the ferrite crystal grains is 10 μm or less. Steel material. 3.5≦(8Mn+3Cr) / (Si+5Mo)≦6.8 (1) Here, each element symbol in formula (1) is substituted with the content of the corresponding element in the aforementioned chemical composition, expressed in mass percent.

2. In mass percent, C: 0.10-0.30%, Si: 0.65-2.00%, Mn: 0.48-1.00%, P: 0.035% or less, S: 0.035% or less, Cr: 0.80-2.00%, Al: 0.010-0.050%, N: 0.0020 to 0.0200%, and, It contains Mo: 0.10-0.35%, Furthermore, it contains one or more selected from the group consisting of Group 1 and Group 2, The remainder consists of Fe and impurities. Satisfying equation (1), In the microstructure, the area ratio of ferrite is 50-70%, the area ratio of bainite is 20% or less, and the remainder consists of pearlite. The average circular equivalent diameter of the ferrite grains is 40 μm or less. The standard deviation of the equivalent circular diameter of the ferrite crystal grains is 10 μm or less. Steel material. [Group 1] Cu: 0.40% or less, Ni: 0.30% or less, Mg: 0.0050% or less, V: 0.50% or less, Nb: 0.050% or less, Ti: 0.050% or less, Ca: 0.0020% or less, B: One or more selected from the group consisting of 0.0040% or less. [Group 2] Bi: 0.020% or less, Pb: 0.060% or less, Sn: 0.100% or less, Sb: 0.050% or less, One or more selected from the group consisting of As: 0.050% or less. 3.5≦(8Mn+3Cr) / (Si+5Mo)≦6.8 (1) Here, each element symbol in formula (1) is substituted with the content of the corresponding element in the aforementioned chemical composition, expressed in mass percent.

3. The steel material according to claim 2, The chemical composition contains the first group, Steel material.

4. The steel material according to claim 2, The aforementioned chemical composition contains the second group, Steel material.

Citation Information

Patent Citations

  • High-strength gear and manufacturing method therefor

    JP2005325398A

  • Manufacturing method of carburized steel part

    JP2020094231A